Marriage Annulment Petitions by KUA Officials: An Analysis from Islamic and Positive Law Perspectives - Fatimah, Fatimah; Purba, Zainal Arifin (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
The practice of marriage annulment petitions filed by KUA (Religious Affairs Office) officials, who were previously responsible for issuing the marriage certificate, raises complex legal and ethical issues. These include questions regarding administrative validity and the professional accountability of the marriage registrar (PPN). This study analyzes the submission of marriage annulment petitions by KUA officials from the perspectives of Islamic law and positive law in Indonesia, concerning Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). Employing a qualitative normative approach, data were collected through a literature review of statutory regulations, classical and contemporary fiqh sources, court decisions, and expert opinions. The findings reveal discrepancies between administrative practices at KUA and the legal standards, particularly in the verification of documents and the legal status of prospective spouses. Common causes of annulments include identity fraud, unlawful polygamy, and administrative errors. From the standpoint of maqashid shari'ah, such annulment actions may be justified to uphold the rights of spouses and their offspring, and to prevent harm resulting from invalid marriages. This research proposes an integrative approach combining Islamic legal principles and national law, and emphasizes the need to strengthen institutional procedures and legal literacy within KUA to ensure the integrity of the marriage system in Indonesia.